Pulsed electromagnetic field stimulation may improve fusion rates in cervical arthrodesis in high-risk populations. Issue 2 (February 2018) - Coric, D.; Bullard, D. E.; Patel, V. V.; Ryaby, J. T.; Atkinson, B. L.; He, D.; Guyer, R. D.
Abstract : Objectives: Pulsed electromagnetic field (PEMF) stimulation was evaluated after anterior cervical discectomy and fusion (ACDF) procedures in a randomized, controlled clinical study performed for United States Food and Drug Administration (FDA) approval. PEMF significantly increased fusion rates at six months, but 12-month fusion outcomes for subjects at elevated risk for pseudoarthrosis were not thoroughly reported. The objective of the current study was to evaluate the effect of PEMF treatment on subjects at increased risk for pseudoarthrosis after ACDF procedures. Methods: Two evaluations were performed that compared fusion rates between PEMF stimulation and a historical control (160 subjects) from the FDA investigational device exemption (IDE) study: a post hoc (PH) analysis of high-risk subjects from the FDA study (PH PEMF); and a multicentre, open-label (OL) study consisting of 274 subjects treated with PEMF (OL PEMF). Fisher's exact test and multivariate logistic regression was used to compare fusion rates between PEMF-treated subjects and historical controls. Results: In separate comparisons of PH PEMF and OL PEMF groups to the historical control group, PEMF treatment significantly (p < 0.05, Fisher's exact test) increased the fusion rate at six and 12 months for certain high-risk subjects who had at least one clinical risk factor of being elderly, a nicotine user, osteoporotic, or diabetic; and for those with at least one clinical risk factor and who received at least a two- or three-level arthrodesis. Conclusion: Adjunctive PEMF treatment can be recommended for patients who are at high risk for pseudoarthrosis. Cite this article : D. Coric, D. E. Bullard, V. V. Patel, J. T. Ryaby, B. L. Atkinson, D. He, R. D. Guyer. Pulsed electromagnetic field stimulation may improve fusion rates in cervical arthrodesis in high-risk populations. Bone Joint Res 2018;7:124–130. DOI: 10.1302/2046-3758.72.BJR-2017-0221.R1.